Legal Analysis of Taxpayer Voluntary Compliance from a Legal Ethics Perspective - Billy Prasetyo; Dhenis Indrawan; Riyzka Alfi Syahraini; Putri Humairah; Khafifah Rizki (ISNU Sumatera Utara, 2024)
This study aims to analyze the contribution of legal and ethical perspectives in building a fair and transparent tax system, particularly in encouraging voluntary taxpayer compliance in Indonesia. This study uses a normative juridical method with a statutory and conceptual approach, to examine how legal rules and moral principles play a role in ensuring the protection of taxpayers' rights during the audit and law enforcement process. The results of the study indicate that the Indonesian tax law system normatively regulates taxpayers' rights and obligations through regulations such as the KUP Law, the Income Tax Law, and the Value Added Tax Law. However, its effectiveness is greatly influenced by the ethics of those implementing it in the field. It was found that the integrity of the apparatus, procedural fairness, and transparency of tax services significantly determine the success of creating a culture of compliance that grows from awareness, not merely fear of sanctions. Therefore, the synergy between legal firmness and the application of ethical values is a key element in national tax system reform.